#TITLE_ALTERNATIVE# - EDO KRISTIANTO NIM : 10714002, BERNARDUS
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia as a result of insulin disorder. Mangosteen rind extract (EM) containing α-mangostin (AM) has an antihyperglicemic activity. This current research was aimed to evaluate the pharmacokinetics (PK) and pharmacodynamics (PD) of EM and AM in repeated dosages. The study was performed on insulin resistance-induced diabetic (DMRI) male Wistar rats induced by high fat and sugar diet. Determination of insulin sensitivity was performed by intraperitoneal glucose tolerance test using rapid acting insulin (1 U/kg BW). EM (248 mg/kg BW/day) and pure AM (37.2 mg/kg BW/day) were given as repeated doses for 14 days. The study was performed in 3 groups, which received EM, pure AM, and the third group as a control, respectively. MFN and AM concentrations in plasma were determined using HPLC. Plasma glucose levels were measured by GOD-PAP method. PK of AM were then calculated. The PD activities of AM were calculated based on area above curve (AAC) values of glucose concentrations. The results of insulin sensitivity test showed a significant improvement after the administration of pure AM for 14 days (0.42 Ã‚Â± 0.26 to 0.85 Ã‚Â± 0.21) and EM for 14 days (0.85 Ã‚Â± 0.08 to 1.35 Ã‚Â± 0.30). The maximum concentration of AM from the administration of EM for 14 days (0.13 Ã‚Â± 0.01 Ã‚Âµg/mL) differed significantly from pure AM for 14 days (0.12 Ã‚Â± 0.00 Ã‚Âµg/mL) and from single EM administration (2.32 Ã‚Â± 32.55 Ã‚Âµg/mL). The time needed to reach the maximum concentration of AM also differed significantly in EM for 14 days (1.375 Ã‚Â± 0.25 hr) compared to single EM (2.00 Ã‚Â± 0.00 hr). The administration of pure AM and EM for 14 days showed a better blood glucose lowering effect, even with a lower AAC (AAC decreased by 74.84%) compared to previous study on single pure AM or metformin.